Linguistic representations of teachers and students of scientific fields at the University - ZIADA, Souheila (Journal of Human Sciences, 2024)
Linguistic representations undoubtedly influence the attitudes, opinions and behaviors of learners with regard to the acquisition either of a given language or of knowledge through a given language. Through this article, which falls within the field of sociolinguistics, we attempt to understand the linguistic representations expressed by teachers and students in scientific fields and their impact on the teaching-learning process.